Outcomes of Transcatheter and Surgical Aortic Valve Replacement in Patients on Maintenance Dialysis - Alqahtani, Fahad (Am J Med, 2017)
BACKGROUND: the introduction of transcatheter aortic valve replacement (TAVR) expanded definitive therapy of aortic stenosis to many high-risk patients, but it has not been fully evaluated in the dialysis population. OBJECTIVES: We aimed to evaluate the current trend and in-hospital outcome of Surgical aortic valve replacement (SAVR) and TAVR in the dialysis population. METHODS: Severe aortic stenosis patients on maintenance dialysis who underwent SAVR or TAVR in the Nationwide Inpatient Sample database (NIS) from January 1, 2005, through December 31, 2014, were included in our comparative analysis. The trends of SAVR and TAVR were assessed. Inhospital mortality, rates of major adverse events, hospital length of stay, cost of care and intermediate care facility utilization were compared between the two groups using both unadjusted and propensity-matched data. RESULTS: Utilization of aortic valve replacement in dialysis patients increased 3-fold with a total of 2,531 dialysis patients who underwent either SAVR (n=2,264) or TAVR (n=267) between 2005–2014 were identified. Propensity score matching yielded 197 matched pairs. After matching, a twofold increase in in-hospital mortality was found with SAVR compared to TAVR 13.7% vs. 6.1% (p=0.021). Patients who underwent TAVR had more permanent pacemaker implantation (13.2% vs. 5.6%, p=0.012), but less blood transfusion (43.7% vs. 56.8% p=0.02). Rates of other key morbidities were similar. Hospital length of stay (19±16 vs. 11±11 days, P<0.001) and non-home discharges (44.7% vs. 31.5%, p=0.002) were significantly higher with SAVR. Cost of hospitalization was 25% less with TAVR. CONCLUSION: TAVR is associated with lower hospital mortality, resource utilization, and cost in comparison with SAVR.